SPATIAL SYNTAX AS A MORPHOLOGICAL APPROACH - da Silva, Antonio Willamys Fernandes; Scharffhausen, Jean-Baptiste Marc Scharffhausen; Santos, Ilanna Clara Macedo; Marques, Yasmin da Conceição; Kraho, Karlessandra Potwyn Souza Lima; Lima, Raquel da Costa; Moura, Isadora Rodrigues; Carvalho, Kamilly Raquel Sousa Meireles; dos Anjos, Sttéphany Romana da Silva (Seven Editora, 2026)
Space Syntax (SS), grounded in the "social logic of space," investigates how urban configuration shapes human behavior and social interactions. This research conducted a bibliometric analysis between 2020 and 2026 in the Web of Science, Scopus, and SciELO databases, using Bibliometrix software to map the scientific production in the field. The results reveal an expanding field, totaling 146 articles and an annual growth rate of 4.91%. A clear geographical shift in production is observed, with China and Australia leading in citation volume, indicating a decentralization from the original European axis. The content analysis of the most relevant publications highlights the integration of SS with hybrid methodologies, such as GIS and Network Analytic Process, applied to themes of public health, socio-spatial equity, and revitalization of historical districts. Seminal studies propose a paradigmatic transition to "evidence-based design," using quantitative and predictive models to optimize urban planning. However, researchers point to limitations in conventional axial modeling, suggesting the refinement of methods to better represent effective accessibility and metric distance. It is concluded that SE is a robust and interdisciplinary scientific tool, essential for understanding and managing the complexity of contemporary urban dynamics.